Serotonin in the solitary tract nucleus shortens the laryngeal chemoreflex in anesthetized neonatal rats - Donnelly, William T. (Exp Physiol, 2016)
The laryngeal chemoreflex (LCR), an airway protective reflex that causes apnea and bradycardia, has long been suspected as an initiating event in the sudden infant death syndrome (SIDS). Serotonin (5-HT) and 5-HT receptors may be deficient in the brainstems of babies who die of SIDS, and 5-HT seems to be important in terminating apneas directly or in causing arousals or as part of the process of autoresuscitation. We hypothesized that 5-HT in the brainstem would limit the duration of the LCR. We studied anesthetized rat pups between 7 and 21 days of age and made microinjections into the cisterna magna or into the nucleus of the solitary tract (NTS). Focal, bilateral microinjections of 5-HT into the caudal NTS significantly shortened the LCR. The 5-HT 1a receptor antagonist, WAY 100635, did not affect the LCR consistently, nor did a 5-HT(2) receptor antagonist, ketanserin, alter the duration of the LCR. The 5-HT(3) specific agonist, 1-(3-chlorophenyl)-biguanide, microinjected bilaterally into the caudal NTS significantly shortened the LCR. Thus, endogenous 5-HT released within the NTS may curtail the respiratory depression that is part of the LCR, and serotonergic shortening of the LCR may be attributed to activation of 5-HT(3) receptors within the NTS. 5-HT(3) receptors are expressed presynaptically on C-fiber afferents of the superior laryngeal nerve, and serotonergic shortening of the LCR may be mediated presynaptically by enhanced activation of inhibitory interneurons within the NTS that terminate during the LCR.